2022
DOI: 10.1123/jpah.2021-0483
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the South African 24-Hour Movement Guidelines for Birth to 5 Years: A Qualitative Study

Abstract: Background: South Africa launched 24-hour movement guidelines for birth to 5 years in 2018. Perceptions of these guidelines were assessed as part of the dissemination process with community-based organizations in 2019. Methods: Fifteen dissemination workshops were held with community-based organization representatives and a range of stakeholders. Discussions were held with workshop attendees (n = 281) to obtain qualitative feedback on the guidelines and workshop. Six follow-up focus groups (n = 28) were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Individual interviews were conducted with key informants ( n = 7) who were purposively recruited to represent the knowledge and practice areas relevant to young children's health behaviors ( 19 21 ). The following participants were deemed knowledgeable of the local context: ECE principal (for children aged 3–6 years), nursery program director (for children aged 2 years and below), education leadership and management consultant, family psychologist, physical fitness specialist, early childhood education academic, and public health academic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual interviews were conducted with key informants ( n = 7) who were purposively recruited to represent the knowledge and practice areas relevant to young children's health behaviors ( 19 21 ). The following participants were deemed knowledgeable of the local context: ECE principal (for children aged 3–6 years), nursery program director (for children aged 2 years and below), education leadership and management consultant, family psychologist, physical fitness specialist, early childhood education academic, and public health academic.…”
Section: Methodsmentioning
confidence: 99%
“…Stakeholders' perceptions comprise one of the most frequently cited components when disseminating information to target audiences ( 16 ). In South Africa, where similar movement guidelines have been launched, the evidence suggests that stakeholders' perceptions helped assess the acceptability of the recommendations to the local population ( 21 ). Qualitative studies have revealed that stakeholders generally found their country-specific movement guidelines acceptable and aligned with health and education priorities ( 19 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders consist of expert representatives from the education and health sectors (e.g., ECE administrators, health researchers), practitioners (i.e., teachers, principals), and parents (14,15). The evidence from countries where similar movement guidelines have been launched suggests that stakeholders' perceptions help assess the acceptability of the recommendations to the local population (16). Qualitative studies have revealed that stakeholders generally found their country-specific movement guidelines acceptable and aligned with health and education priorities (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from countries where similar movement guidelines have been launched suggests that stakeholders' perceptions help assess the acceptability of the recommendations to the local population (16). Qualitative studies have revealed that stakeholders generally found their country-specific movement guidelines acceptable and aligned with health and education priorities (14)(15)(16). Barriers to uptake of the guidelines have also been identified, such as lack of available information, daily activities that compete for time and resources, challenges associated with current social norms (14), and high usage of technologybased devices at home (15).…”
Section: Introductionmentioning
confidence: 99%